Case Report: Primary Hypothyroidism Associated With Lutetium 177-DOTATATE Therapy for Metastatic Paraganglioma - Gubbi, Sriram; Al-Jundi, Mohammad; Del Rivero, Jaydira; Jha, Abhishek; Knue, Marianne; Zou, Joy; Turkbey, Baris; Carrasquillo, Jorge Amilcar; Lin, Emily; Pacak, Karel; Klubo-Gwiezdzinska, Joanna; Lin, Frank I-Kai (Frontiers in Endocrinology, 2021)
Background: Lutetium 177 (177Lu) - DOTATATE is a form of peptide receptor radionuclide therapy (PRRT) that is utilized in the treatment of neuroendocrine tumors. There is limited data on 177Lu-DOTATATE-induced thyroid dysfunction. Case Description: A 29-year-old male with SDHB positive metastatic paraganglioma enrolled under the 177Lu-DOTATATE trial (NCT03206060) underwent thyroid function test (TFT) evaluation per trial protocol prior to treatment with 177Lu-DOTATATE. The thyroid stimulating hormone (TSH) was suppressed [<0.01 µIU/mL (0.27 - 4.2 µIU/mL)], with normal free thyroxine (FT4) [1.3 ng/dL (0.9 - 1.7 ng/dL)], and elevated total triiodothyronine (T3) 235 ng/dL (65 – 193 ng/dL). The TSH receptor antibody and thyroid stimulating immunoglobulin index were <1 IU/L (1000 IU/mL), and anti-Tg antibodies (668 IU/mL) had substantially increased, with concomitant reductions in FT4 (0.3 ng/dL) and total T3 [54 ng/dL (87 – 169 ng/dL)]. Diffuse thyroid uptake was noted on a diagnostic gallium 68 - DOTATATE positron emission tomography-computed tomography (PET/CT) performed prior to 177Lu-DOTATATE treatment. Post-therapy single-photon emission computed tomography (SPECT) also revealed diffuse uptake of 177Lu-DOTATATE in the thyroid gland. The patient was started on levothyroxine therapy and his symptoms resolved. Summary: We report, for the first time, a patient with an initial diagnosis of asymptomatic primary hyperthyroidism who rapidly developed symptomatic primary hypothyroidism one month after 177Lu-DOTATATE therapy, accompanied by marked changes in TFTs and thyroid auto-antibody titers, along with functional imaging evidence of diffuse uptake of 177Lu-DOTATATE in the thyroid gland. Conclusions: Thyroid dysfunction can be associated with PRRT. Thyroid uptake patterns on pre-treatment diagnostic somatostatin analogue scans might predict individual susceptibility to PRRT-associated TFT disruption. Therefore, periodic evaluation of TFTs should be considered in patients receiving PRRT.